Analisis Hukum Peraturan Daerah Kabupaten Magelang tentang Agrowisata (International Forum of Researchers and Lecturers, 2025)
Magelang Regency, Central Java, has great potential in the agrotourism sector that can contribute to the local economy and the preservation of cultural values. This study aims to design an Agrotourism Law that regulates the management, development, and protection of the environment in the area. The research method used is empirical juridical, which involves collecting primary data from local communities and analyzing existing regulations. The results of the study indicate that the development of agrotourism in Magelang Regency is still hampered by the lack of coordination and unclear regulations, which can trigger environmental exploitation and injustice in the distribution of economic benefits. Therefore, the drafted law must include regulations on sustainable management, rights and obligations of business actors, environmental protection, promotion of local culture, and financial support for community-based agrotourism. This study is expected to be a reference in formulating policies that are beneficial for the development of sustainable and inclusive agrotourism in Magelang Regency.